KdmA, a histone H3 demethylase with bipartite function, differentially regulates primary and secondary metabolism in Aspergillus nidulans. Issue 4 (11th April 2015) - Gacek‐Matthews, Agnieszka; Noble, Luke M.; Gruber, Clemens; Berger, Harald; Sulyok, Michael; Marcos, Ana T.; Strauss, Joseph; Andrianopoulos, Alex
Summary A spergillus nidulans kdmA encodes a member of the KDM4 family of jumonji histone demethylase proteins, highly similar to metazoan orthologues both within functional domains and in domain architecture. This family of proteins exhibits demethylase activity towards lysines 9 and 36 of histone H3 and plays a prominent role in gene expression and chromosome structure in many species. Mass spectrometry mapping of A. nidulans histones revealed that around 3% of bulk histone H3 carried trimethylated H3K9 (H3K9me3) but more than 90% of histones carried either H3K36me2 or H3K36me3. KdmA functions as H3K36me3 demethylase and has roles in transcriptional regulation. Genetic manipulation of KdmA levels is tolerated without obvious effect in most conditions, but strong phenotypes are evident under various conditions of stress. Transcriptome analysis revealed that – in submerged early and late cultures – between 25% and 30% of the genome is under KdmA influence respectively. Transcriptional imbalance in the kdmA deletion mutant may contribute to the lethal phenotype observed upon exposure of mutant cells to low‐density visible light on solid medium. Although KdmA acts as transcriptional co‐repressor of primary metabolism genes, it is required for full expression of several genes involved in biosynthesis of secondary metabolites.